Integrated Design of Multimode and Multifrequency Miniaturized Handset Antenna at VHF/UHF Bands - Yandong Zhang; Hui Zhang; Liang Xu; Linao Li; Chunxiao Li; Zhijuan An (International Journal of Antennas and Propagation)
This paper presents an integrated design of a multimode and multifrequency miniaturized handset antenna working at the lower band (0.24–0.7 GHz) with linear polarization and higher band (1.98–2.01 GHz and 2.17–2.20 GHz) with circular polarization simultaneously. At the higher band, the quadrifilar helix antenna (QHA) is utilized with each arm developed into two arms of different lengths and linearly tapered widths to realize double resonance and increase the bandwidth. Moreover, a helical stub behaving as a director is introduced to improve the antenna gain. At the lower band, the outer conductor of the QHA feedline and four QHA arms are designed to constitute a monopole antenna through proper feeding and introducing four quarter-wavelength short-circuit stubs. With this radiator-sharing technique, the QHA not only works at the higher band with a circular polarization pattern but can act as a monopole antenna working at the lower band with a linear polarization pattern simultaneously. As a result, the size of the antenna can be reduced remarkably. Finally, the proposed antenna is fabricated with a total length of 228 mm and a diameter of 15 mm. At the lower band, the measured S11 is below −8 dB, and the gain is larger than 0.5 dBi. At the higher band, the measured S11 and AR are better than −13 dB and 3 dB, respectively, and the gain within the zenith angle range of 0°−35° is greater than 2.5 dBi, which demonstrates better performance.